Cycle indices of PGL(2,q) acting on the cosets of its subgroups - Rotich, S.K (International Journal of Scientific Research and Innovative Technology, 2017)
In this paper, we mainly investigate the action of 𝑃𝐺𝐿 2,𝑞 on the cosets some of its subgroups namely; 𝐶𝑞−1,𝐶𝑞+1and 𝑃 𝑞. Corresponding to each action the disjoint cycle structures and cycle index formulas is determined.
Keywords: Disjoint cycle structures; Cycle index formula